2015
DOI: 10.1007/s10488-015-0653-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Activation and Mental Health Care Experiences Among Women Veterans

Abstract: We utilized a nationally representative survey of women veteran primary care users to examine associations between patient activation and mental health care experiences. A dose–response relationship was observed, with odds of high quality ratings significantly greater at each successive level of patient activation. Higher activation levels were also significantly associated with preference concordant care for gender-related preferences (use of female providers, women-only settings, and women-only groups as oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Our findings add to previous studies reporting lower patient activation scores among minority groups, specifically, African-Americans, Hispanics, and non-native English speakers (Lubetkin, Zabor, Brennessel, Kemeny, & Hay, 2014). Moreover, a recent study showed that African-American female veterans had significantly lower levels of patient activation compared to their White counterparts, and their scores correlated with less positive ratings of mental healthcare experiences (Kimerling, Pavao, & Wong, 2016). Our study provides additional evidence indicating lower levels of patient activation among minority groups and demonstrates an association between race, patient activation, and working alliance.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings add to previous studies reporting lower patient activation scores among minority groups, specifically, African-Americans, Hispanics, and non-native English speakers (Lubetkin, Zabor, Brennessel, Kemeny, & Hay, 2014). Moreover, a recent study showed that African-American female veterans had significantly lower levels of patient activation compared to their White counterparts, and their scores correlated with less positive ratings of mental healthcare experiences (Kimerling, Pavao, & Wong, 2016). Our study provides additional evidence indicating lower levels of patient activation among minority groups and demonstrates an association between race, patient activation, and working alliance.…”
Section: Discussionsupporting
confidence: 78%
“…One important factor to consider when examining gender differences among VA users is that women Veterans remain underrepresented in treatment and research (Rohrer et al, 2011) despite the recent emphasis on providing gender-specific care (Kimerling, Pavao, & Wong, 2015; Yano et al, 2009; Yano & Frayne, 2011). For example, women are currently underrepresented in SUD treatments studies (Cucciare, Simpson, Hoggatt, Gifford, & Timko, 2013) and intervention studies overall.…”
Section: Discussionmentioning
confidence: 99%
“…36 Higher activation measured with the Patient Activation Measures Questionnaire 36 is associated with preferences for involvement in medical decision making, 37,38 and is associated with better reported healthcare experiences and with preference for sex-concordant care in women veterans. 39 Decision-making style is the characteristic mode of perceiving and responding to decision-making tasks. 40,41 The General Decision-Making Inventory 42 categorizes individuals' decision-making styles.…”
Section: Cognitive Factorsmentioning
confidence: 99%